2013
DOI: 10.1007/s10593-013-1217-1
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-free synthesis of novel 5-oxo-5H-chromeno[4,3-b]pyridine derivatives

Abstract: An efficient and simple method for the synthesis of new 5-oxo- 5H-chromeno[4,3-b]pyridine derivatives via Michael addition of 4-aminocoumarin to arylidenemalononitrile for 20 min at 150°C without any solvent is proposed. The advantages of this procedure are mild reaction conditions, high yields of products, and operational simplicity.Keywords: 5-oxo-5H-chromeno [4,3-b]pyridine, Michael addition, solvent-free synthesis.Various coumarin derivatives, particularly those fused with other heterocycles, have attracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It was suggested that lactic acid aids the process by interacting with the adduct via hydrogen bonding, facilitating the Michael addition step. Motamendi presented a solvent-free methodology for the synthesis of chromenopyridine derivatives 122, through the reaction of 4-aminocoumarin 114 with arylidenemalononitriles 121, at 150 °C [93]. The final product was obtained after flash chromatography purification, with isolated yields of 60-80%.…”
Section: Coumarinsmentioning
confidence: 99%
“…It was suggested that lactic acid aids the process by interacting with the adduct via hydrogen bonding, facilitating the Michael addition step. Motamendi presented a solvent-free methodology for the synthesis of chromenopyridine derivatives 122, through the reaction of 4-aminocoumarin 114 with arylidenemalononitriles 121, at 150 °C [93]. The final product was obtained after flash chromatography purification, with isolated yields of 60-80%.…”
Section: Coumarinsmentioning
confidence: 99%
“…pounds of this type are usually obtained from 3-substituted coumarins, [23,[26][27][28][29] 4-substituted coumarins, [30][31][32][33][34][35] salicylic aldehydes, [36] 2-halobiarylcarboxylates, [37] or halogenated arenecarboxylates [38] by means of catalytic processes. Several authors have communicated the synthesis of 5-hydroxy-5Hbenzopyrano [4,3-b]pyridine, a reduced precursor of the pyrido [3,2-c]coumarin core structure, starting from 3-formylchromone.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrido[3,2‐ c ]coumarins are important because of their photophysical and biological effects as well as their potential applications, for example, bright fluorescence, chemosensory properties, fluorescence imaging in living cells, decrease of blood sugar levels, and positive inotropic effects . Compounds of this type are usually obtained from 3‐substituted coumarins,, 4‐substituted coumarins, salicylic aldehydes, 2‐halobiarylcarboxylates, or halogenated arenecarboxylates by means of catalytic processes. Several authors have communicated the synthesis of 5‐hydroxy‐5 H ‐benzopyrano[4,3‐ b ]pyridine, a reduced precursor of the pyrido[3,2‐ c ]coumarin core structure, starting from 3‐formylchromone .…”
Section: Introductionmentioning
confidence: 99%